Association of rs2072446 in the NGFR gene with the risk of Alzheimer's disease and amyloid‐β deposition in the brain. (8th September 2022) - He, Chen‐Yang; Wang, Zuo‐Teng; Shen, Ying‐Ying; Shi, An‐Yu; Li, Hui‐Yun; Chen, Dong‐Wan; Zeng, Gui‐Hua; Tan, Cheng‐Rong; Yu, Jin‐Tai; Zeng, Fan; Wang, Yan‐Jiang; ,
Abstract: Introduction and Aims: Alzheimer's disease (AD) is the most common form of dementia with a complex genetic background. The cause of sporadic AD (sAD) remains largely unknown. Increasing evidence shows that genetic variations play a crucial role in sAD. P75 neurotrophin receptor (p75NTR, encoded by NGFR ) plays a critical role in the pathogenesis of AD. Yet, the relationship between NGFR gene polymorphisms and AD was less studied. This study aims to analyze the relationship of NGFR gene polymorphism with the risk of AD in the Chinese Han population and amyloid‐β deposition in the ADNI cohort. Methods: This case–control association study was conducted in a Chinese Han cohort consisting of 366 sporadic AD (sAD) patients and 390 age‐ and sex‐matched controls. Twelve tag‐SNPs were selected and genotyped with a multiplex polymerase chain reaction‐ligase detection reaction (PCR‐LDR) method. The associations between tag‐SNPs and the risk of AD were analyzed by logistic regression. Moreover, another cohort from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database was included to examine the association of one tag‐SNP (rs2072446) with indicators of amyloid deposition. Kaplan–Meier survival analysis and Cox proportional hazards models were used to test the predictive abilities of rs2072446 genotypes for AD progression. The mediation effects of Aβ deposition on this association were subsequently tested by mediation analyses. Results: After multiple testing corrections, one tag‐SNP, rs2072446, was associated with an increased risk of sAD (additive model, OR = 1.79, P adjustment = 0.0144). Analyses of the ADNI cohort showed that the minor allele (T) of rs2072446 was significantly associated with the heavier Aβ burden, which further contributed to an increased risk of AD progression in APOE ε4 non‐carrier. Conclusion: Our study found that rs2072446 in NGFR is associated with both the risk of sAD in the Chinese Han population and the amyloid burden in the ADNI cohort, which reveals the role of p75NTR in AD from a genetic perspective. Abstract : rs2072446 in the NGFR gene increases the risk of sAD in Chinese Han population and is also correlated with higher amyloid burden and an increased risk for AD progression in the APOE ε4 non‐carriers from the ADNI cohort, which represents a novel AD risk locus.